L’apport du diagnostic archéologique pour la lecture d’un bâti « ordinaire » : l’église de Nozières (Cher) - Victorine Mataouchek (Bulletin du Centre d’Études Médiévales d’Auxerre)
Prescribed in order to back up restoration work, the archaeological study of Saint-Paxent’s church in Nozières – a modest-looking building – revealed the presence of an unsuspected potential. Beyond the new light provided by this study on the Early medieval origin of the building, the whole history of this small parish church deserves attention. This study shows how useful it would be to generalize the archaeological investigation of these so-called « minor elements » which, however, constitute the bulk of the monumental landscape.